Perceived Immigrant Threat and Punitive Attitudes: The Moderating Effect of Economic Insecurity. (April 2022) - Trahan, Adam; Pierce, Kelly
One of the strongest predictors of punitive attitudes is out-group prejudice. Two limitations of this literature are a relative lack of research examining (a) these relationships outside the United States and (b) the theoretical mechanisms involved. The current study tests the direct and moderating effects of group threat and economic insecurity on punitive attitudes among German citizens. Findings show the direct effect of group threat on punitive attitudes was significant and positive in three OLS regression models measuring different perceptions of threat by immigrants. The direct effect of economic insecurity on punitive attitudes was non-significant, but economic insecurity had a significant moderating effect on out-group prejudice and punitiveness in all three models.